Land Use Changes Analysis in Jakarta Bay Coastal Area Between 1998, 2008 and 2018 - Anwar Rizal; Fikri Haykal (Politeknik Kelautan dan Perikanan Dumai, 2021)
As the national capital and one of the largest cities in the world, environmental conditions and land use in Jakarta have changed a lot in the last twenty years. Economic growth and high population growth in Jakarta have resulted in massive development of infrastructure and residential areas in Jakarta. Economic growth and an increase in population are become problems, especially with the decreasing of green areas due to the development process carried out without paying attention to the surrounding environment. Environmental problems such as water pollution, land subsidence, coastal erosion and flooding often occur in the Jakarta area, especially in the coastal areas of North Jakarta. Here, we used Landsat image data to compare land-use conditions in the coastal areas of Jakarta in the period of 1998- 2018. The research showed that the area of mangrove has increased by 79 hectares during 1998 -2018 period. likewise, the built-up areas and open land increased by 292 hectares and 887 hectares respectively. Meanwhile, the area of vegetation, water bodies, and fishpond has decreased by 393 hectares, 797 hectares and 309 hectares respectively. Development and reclamation have changed land-use in the Northern area of Jakarta. However, it is also necessary to pay attention to the impact of development on environmental and social conditions in the North Jakarta area.